2016
DOI: 10.1097/scs.0000000000002444
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Cephalometric Measures and End-of-Treatment Facial Attractiveness

Abstract: Sixty-nine experienced Chinese orthodontists evaluated 108 Chinese patients' facial attractiveness from set of photographs (frontal, lateral, and frontal smiling photos) taken at the end of orthodontic treatment. These 108 patients, which contained an equal number of patients with Class I, II, and III malocclusion, were randomly selected from 6 orthodontic treatment centers throughout China. Spearman rank-order correlation coefficients (rs) analyses were performed to examine agreement in ranking between all ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
1
15
1
Order By: Relevance
“…But clinically, this difference cannot be considered relevant. Leichsenring et al 12 found a mean of 71.75 degrees and Yu et al 13 found a mean of 68.33 for the Z-Angle in a study conducted with Chinese patients with normal occlusion and balanced profiles, values lower than the 77.93 degrees found in this study. This is probably due to age differences between the samples and can be attributed to the early maturation of girls 14 .…”
Section: Discussioncontrasting
confidence: 45%
“…But clinically, this difference cannot be considered relevant. Leichsenring et al 12 found a mean of 71.75 degrees and Yu et al 13 found a mean of 68.33 for the Z-Angle in a study conducted with Chinese patients with normal occlusion and balanced profiles, values lower than the 77.93 degrees found in this study. This is probably due to age differences between the samples and can be attributed to the early maturation of girls 14 .…”
Section: Discussioncontrasting
confidence: 45%
“…3 In the present study, higher facial inclination of maxil- enough, especially in patients with anterior crowding. 17,35 Further…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the present retrospective study may potentially affect the data explanation. For example, the perception of incisor inclination and smiling by the clinicians, patients and their parents would fundamentally affect the final position of incisors to lips, thereby impacting cephalometric inclination of upper and lower incisors 35 . In addition, lack of case randomization as well as clinical preference of the appliances may contribute to a selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the core situation of facial beauty in our orthodontic specialty, the definition of facial attractiveness is still a matter of debate. 3 – 5 Esthetical standards are subjective opinions which vary with every individual, influenced by occupational experiences, regional disparities, ethnicities and genders. 3 , 6 9 The deviation between orthodontists and patients about aesthetics has become a relevant point on the satisfaction of the orthodontic treatment.…”
mentioning
confidence: 99%